Nephrotic Syndrome in a Patient with Metastatic Melanoma: Beyond the Obvious - Messias, A (2019)
Nephrotic syndrome in a patient with metastatic melanoma can occur in the context of a paraneoplastic glomerulopathy or as a complica tion of treatment. New oncologic immunotherapies, including immune checkpoint inhibitors, have been frequently associated with interstitial nephritis and, in rare cases, with nephrotic syndrome. This article presents the case of a 52 -year -old man diagnosed with metastatic melanoma who was admitted with acute kidney injury and nephrotic syndrome after having started immune checkpoint inhibitors. After investigation, acute kidney injury was attributed to immunotherapy -associated acute interstitial nephritis, and nephrotic syndrome was found to be the result of AA amyloidosis, which is a rare complication of metastatic melanoma.